Morphological characterization and molecular profiling of malignant pericardial effusion in patients with pulmonary adenocarcinoma - Bing Zhou; Lin Li; Dayou Shi; Tao Jiang; Guohui Xue; Jianping Xiong (Wolters Kluwer Medknow Publications, 2019)
Context: Malignant pericardial effusions (MPCEs) is a common complication observed in advanced pulmonary adenocarcinoma. In such cases, investigating molecular alterations can have significant therapeutic implication in determining anticancer drugs. Aim: The objective was to evaluate the significance of cell block technique in the diagnosis of MPCE and further investigate the morphological and molecular profiles of MPCE in patients with pulmonary adenocarcinoma. Setting and Design: Cytopathological and molecular profiles of 19 MPCE cases in patients with pulmonary adenocarcinoma were retrospectively analyzed. The control group consisted of 14 malignant pleural effusion (MPE) cases in patients with pulmonary adenocarcinoma. Materials and Methods: Anaplastic lymphoma kinase (ALK) and tyrosine-protein kinase Met (C-MET) expression was evaluated by fluorescence in situ hybridization (FISH). Epithelial growth factor receptor (EGFR) and K-Ras (KRAS) mutations were detected by ARMS real-time polymerase chain reaction (RT-PCR). Statistical Analysis Used: Associations between MPCE and MPE were analyzed using Fisher's exact test. Results: MPCE was found to have micropapillary and solid pattern predominant with mucin secretion compared to acinar patterns, as seen in MPE. Seventeen MPCE cases (89.5%) and all MPE cases (100%) underwent molecular analysis. Mutations in EGFR and KRAS, ALK rearrangement, and C-MET amplification were observed in MPCE and MPE with statistical differences. Additionally, two MPCE cases demonstrated EGFR T790M mutation and multiple insertions at L858. Conclusions: MPCE shows micropapillary and solid cytological patterns predominant with mucin secretion. MPCE are suitable to analyze oncogenic mutations and to develop targeted therapy for patients with pulmonary adenocarcinoma. Further molecular investigations may reveal novel molecular alterations.